FEATURES OF VALUATION OF STARTUP PROJECTS IN ENTREPRENEURIAL ACTIVITY - KALINSKY, Eugen; EVTUSHENKO, Valentina (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Startup valuation, an intricate endeavor due to the unique characteristics of these entities, presents distinct challenges when compared to the valuation of well-established companies. This article examines the complexities inherent in valuing startups, shedding light on the absence of historical data, heightened levels of risk associated with startups and their dynamic environments, the inherent uncertainty in forecasting future development, and the pronounced influence of intangible assets on the overall business valuation.In addressing the valuation of startups, several methods are explored, each with its advantages and limitations. The scenario-based approach, encompassing a range of potential outcomes from successful to failure scenarios, provides a comprehensive assessment of startup value. Additionally, the venture capital method, relying on expected company value at the investor's exit point, enables valuation without the need for exhaustive cash flow forecasting. These methods take into account the unique dynamics of startup growth and risk.Furthermore, the article stresses the significance of meticulous market analysis, rigorous evaluation of company potential, examination of industry-specific data, and careful consideration of tax incentives. These factors are crucial for a thorough understanding of the startup's financial health and future trajectory, which directly impacts its value.To achieve a more objective and accurate valuation, it is recommended to employ a combination of valuation methods, considering the startup's stage of development and specific characteristics. Diverse data sources, including empirical studies and industry benchmarks, can enhance the accuracy of estimates.In conclusion, the article asserts the importance of advancing startup valuation methodologies. Drawing from international experience and conducting in-depth research in specific areas can lead to improved precision, enhanced objectivity, and reduced risks of errors in the valuation process. By refining the valuation techniques, stakeholders can make more informed investment decisions and contribute to the growth of the vibrant startup ecosystem.
Keywords: startups; valuation; valuation methods; entrepreneurship